Response of Food-Webs Indicators to Human Pressures, in the Scope of the Marine Strategy Framework Directive - Machado, Inês; Costa, José Lino; Cabral, Henrique (Frontiers in Marine Science, 2021)
Understanding food webs environmental condition is a challenging task since evaluations are limited by data on key ecosystem elements, by the availability of indicators that incorporate relevant guilds and by the difficulty in establishing cause-effect relations between pressures and health status, as multiple overlapping pressures can affect taxonomic elements differently. The present work aims to investigate food webs assessment under the Marine Strategy Framework Directive (MSFD), revealing gaps and future research needs in the North Eastern Atlantic. To understand reporting patterns, information on the criteria employed and the resulting assessment trends of Descriptor 4—Food webs were surveyed from the MSFD reports. A multivariate analysis was applied to food webs assessment status and spatially overlapping anthropogenic pressures to understand if the assessment was detecting pressures, considering fish elements. Results revealed that reporting strategies varied between Member States. High reporting effort was exhibited by the United Kingdom in opposition to Ireland or France. Reporting of other groups other than fish and plankton was limited to the United Kingdom due to the availability of monitoring programs and data. The analysis applied to criteria considering fish elements reinforced that reporting strategies and trends differed between countries, although some similarities were found for the Bay of Biscay and Iberian coast and the Celtic Seas. Food webs assessment trends for fish were variable in Spain and were stable or increased in Portugal and the United Kingdom. Anthropogenic drivers significantly influencing food web trends for fish elements were fishing, and climate anomalies in the southern Bay of Biscay and Iberian coast, while eutrophication and chemical contamination had effects on trends in the Celtic Sea and the North Sea. Results allowed to establish a relation between anthropogenic effects and food web patterns, however, these were limited since food webs assessment is incongruent in terms of criteria used and data is still limited at relevant scales. This study reinforced the necessity to increase Member States harmonization and calibration to improve our understanding of food webs environmental status.